Interrelationship between implant and orthognathic surgery for the rehabilitation of edentulous cleft palate patients: a case report - José Fernando Scarelli LOPES; João Henrique Nogueira PINTO; Monica Moraes Waldemarin LOPES; Reinaldo MAZOTTINI; Simone SOARES (Journal of Applied Oral Science, 2015)
A 43-year-old woman with a unilateral cleft lip and palate, presenting a totally edentulous maxilla and mandible with marked maxillomandibular discrepancy, attended the Prosthodontics section of the Hospital for Rehabilitation of Craniofacial Anomalies, University of São Paulo for treatment. She could not close her mouth and was dissatisfied with her complete dentures. Treatment planning comprised placement of six implants in the maxilla, four in the mandible followed by prostheses installation and orthognathic surgery. The mandibular full arch prosthesis guided the occlusion for orthognathic positioning of the maxilla. The maxillary complete prosthesis was designed to assist the orthognathic surgery with a provisional prosthesis (no metal framework), allowing reverse treatment planning. Maxillary and mandibular realignment was performed. Three months later, a relapse in the position of the maxilla was observed, which was offset with a new maxillary prosthesis. This isa complex interdisciplinary treatment and two-year follow-up is presented and discussed. It should be considered that this type of treatment could also be applied in non-cleft patients.